Intradialytic Myocardial Stunning in Hemodialysis Dependent End Stage Kidney Disease - David M. Charytan; James B. Wetmore; Charles A. Herzog (Clinical Journal of the American Society of Nephrology, 2026)
People with hemodialysis-dependent kidney failure have a high incidence of cardiovascular morbidity and mortality, the etiologies of which remain incompletely understood. Recent work has suggested that the hemodialysis procedure itself induces transient episodes of myocardial contractile dysfunction, a phenomenon known as intradialytic myocardial stunning (IDMS). IDMS likely results in repetitive injury to the heart and, as such, may be an underappreciated risk factor which at least partly underlies the high rate of cardiovascular events in this population. However, many important questions about IDMS remain. In this manuscript, we review the evidence base on IDMS. First, we provide a proposed working definition of this entity, placing it within the historical context of other syndromes of transient myocardial contractile abnormalities such as those caused by ischemia or by neurogenic (stress) cardiomyopathy. We then outline the seminal evidence supporting the hypothesis that IDMS is a specific form of Tako-tsubo (stress) cardiomyopathy. We next discuss the epidemiology of IDMS, including incidence, risk factors, sequelae, and potential contributions to the development of cardiovascular disease in people receiving maintenance hemodialysis. Finally, we focus on the frontiers of IDMS research by identifying avenues of future study, including potential mechanisms which can be investigated using novel techniques, and identify gaps in the current understanding of IDMS which provide a roadmap for future studies.